A 'just' hydrogen economy: A normative energy justice assessment of the hydrogen economy. (October 2022) - Dillman, K.J.; Heinonen, J.
Abstract: The climate crisis, the renewed importance of energy security and geopolitics, and economic interests are fuelling interest in the hydrogen economy. While still in its nascency, if financial and political commitments are an indication, the hydrogen economy is likely to rapidly develop. Many scholars have noted, however, the significant lack of social assessments of the hydrogen economy. This work addresses this gap through a normative energy justice assessment across the hydrogen economy value chain to provide an initial proactive mapping of potential energy injustices that could occur from its development across four injustice perspectives (distribution, procedural, cosmopolitan, and recognition). Further, this work suggests potential abatement actions that could be taken to reduce the identified injustices. Lacking research on the social impacts of the hydrogen economy due to its nascency, this work benchmarks to energy justice assessments as well as abating actions from other transitions to provide this first mapping. The results of this work show that potential injustices could arise from unjust decision-making, socially irresponsible development, and the poor sharing of ills/benefits on the consumption end. While the hydrogen economy's development pathway is still largely unknown, this work hopes to provide foresight to policymakers and future researchers (who can then study them in more detail) about potential injustices along the hydrogen value chain with the goal of avoiding or reducing them. Being aware of and reducing these injustices during the development of the hydrogen economy should serve to foster public support for its proliferation. Graphical abstract: Image 1 Highlights: A proactive systemic overview of social impacts across the hydrogen economy is needed. Energy justice assessment used to provide a first mapping of potential injustice drivers and impacts across it. Abatement actions for these injustices were further suggested. Results showed that social injustices could occur across the value chain. Policy makers should address these social injustices when formulating hydrogen policies.